Discriminative-stimulus effects of second generation synthetic cathinones in methamphetamine-trained rats. (1st April 2015) - Naylor, Jennifer E.; Freeman, Kevin B.; Blough, Bruce E.; Woolverton, William L.; Huskinson, Sally L.
Highlights: We tested the discriminative stimulus effects of second-generation synthetic cathinones in methamphetamine-trained rats. Alpha-PVP and 4-MePPP both substituted for methamphetamine. 4-MEC did not substitute for methamphetamine. Abstract: Background: Synthetic cathinones are beta-ketophenethylamine analogs manufactured to avoid legal restrictions placed on illicit stimulants like methamphetamine. Regulating these "emerging" designer drugs require scientific evidence of abuse potential. Methods: The present study evaluated the discriminative-stimulus effects of three synthetic cathinones, recently identified in commercial and confiscated products, in male Sprague-Dawley rats trained to discriminate methamphetamine (1.0 mg/kg) from saline under a fixed-ratio (FR) 20 schedule of food delivery. Three synthetic cathinones, 4-methyl-N-ethylcathinone (4-MEC; 1.0–8.0 mg/kg), 4-methyl-alpha-pyrrolidinopropiophenone (4-MePPP; 4.0–16.0 mg/kg), and alpha-pyrrolidinopentiophenone (alpha-PVP; 0.25–2.0 mg/kg) were tested for their ability to substitute for methamphetamine. Results: Full substitution for the training dose of methamphetamine occurred at the highest doses for both 4-MePPP and alpha-PVP, and 4-MEC did not substitute at any dose tested. Conclusions: The present findings show that two synthetic cathinones, 4-MePPP and alpha-PVP, produced subjective effects similar to those of methamphetamine. The synthetic cathinone, 4-MEC, did not produce subjective effects similar to those of methamphetamine with the parameters used in the current experiment. Based on findings here and by others, these three compounds warrant further tests of abuse potential.